Global insights into [177Lu]Lu-DOTATATE safety: a comprehensive disproportionality analysis from the WHO pharmacovigilance database - Ladrière, Typhanie; Chrétien, Basile; Bignon, Anne-Laure; Bouhier‐Leporrier, Karine; Dolladille, Charles; Vigne, Jonathan (Scientific Reports, 2026)
Peptide receptor radionuclide therapy with [177Lu]Lu-DOTATATE is an effective treatment for metastatic or inoperable neuroendocrine tumors. While clinical trials have demonstrated its efficacy and safety in a limited number of selected patients, real-world data on [¹⁷⁷Lu]Lu-DOTATATE remain scarce. This study aims to investigate the safety profile of [¹⁷⁷Lu]Lu-DOTATATE in a real-world setting using VigiBase, the World Health Organization’s global pharmacovigilance database. A retrospective disproportionality analysis was conducted on individual case safety reports from VigiBase using a deduplicated dataset. Signal detection was performed using the information component (IC) with a 95% credibility interval (IC₀₂₅) to assess the association between each adverse drug reaction (ADR) and [¹⁷⁷Lu]Lu-DOTATATE. A total of 3,984 reports were analyzed. Associations were identified for hematologic malignancies, hematological disorders, hepatic disorders, renal toxicity, and infections (IC₀₂₅ = 2.48, 2.15, 1.43, 1.16, and 0.91, respectively). Notably, certain gastrointestinal disorders initially significant saw their IC₀₂₅ values turn negative over time, while other ADR categories remained consistently positive. Key overlaps between ADR categories were observed, supported by coherent time-to-onset data and positive [¹⁷⁷Lu]Lu-DOTATATE dechallenge. This VigiBase analysis reveals essential information on ADR associated with [177Lu]Lu-DOTATATE providing a complete safety profile with real-life data enabling better patient management.